Gender and life-cycle differentials in the correlates of adult ill health in South Africa - Maboshe, Mashekwa (School of Economics, 2015)
This study investigates the gender and life-cycle differentials in the socio-economic co-variates of adult self-evaluated ill health in South Africa using data from the 2008 National Income Dynamics Study wave 1 survey.